1986
DOI: 10.1055/s-2007-1020415
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature, Mean Arterial Pressure, and Cardiopulmonary Bypass Flows on Somatosensory Evoked Potential Latency in Man

Abstract: Median nerve somatosensory evoked potentials were recorded in 21 patients undergoing cardiac surgical procedures utilizing cardiopulmonary bypass, in order to establish the effects of hypothermia, reductions in mean arterial pressure, and alterations in cardiopulmonary bypass flows on evoked potential latency. Induction and maintenance of anesthesia with fentanyl caused a significant prolongation of latency of the first cortical peak. Temperature changes were linearly correlated with changes in latency for pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In another study from the same laboratory, central conduction times were reported to increase 6.6%/"C decrease in t e m p e r a t~r e .~~ Fairly linear increases in absolute latencies of posterior tibia1 SEPs (popliteal fossa, lumbar spinal cord, and cortex) were reported with hypothermia down to 25OC-28"C by others as well. 30 In one study, larger than 1.5 m/"C increases in the latency to the first positive cortical peak was considered reason for concern and intervention.lo4 Nasopharyngeal temperatures were found to correlate well with the observed changes, but not rectal or limb temperatures. Amplitude changes of scalp SEPs in hypothermia do not correlate well with temperature, yet they are usually reduced lo4; this is most likely the result of desynchronization in the afferent central pathways similar to that observed in peripheral nerves.…”
Section: Somatosensory Evoked Potentialsmentioning
confidence: 98%
“…In another study from the same laboratory, central conduction times were reported to increase 6.6%/"C decrease in t e m p e r a t~r e .~~ Fairly linear increases in absolute latencies of posterior tibia1 SEPs (popliteal fossa, lumbar spinal cord, and cortex) were reported with hypothermia down to 25OC-28"C by others as well. 30 In one study, larger than 1.5 m/"C increases in the latency to the first positive cortical peak was considered reason for concern and intervention.lo4 Nasopharyngeal temperatures were found to correlate well with the observed changes, but not rectal or limb temperatures. Amplitude changes of scalp SEPs in hypothermia do not correlate well with temperature, yet they are usually reduced lo4; this is most likely the result of desynchronization in the afferent central pathways similar to that observed in peripheral nerves.…”
Section: Somatosensory Evoked Potentialsmentioning
confidence: 98%